Hubungan Kualitas Tidur dan Fungsi Kognitif Siswa MAN Binjai - Fachlefi, Said; Rambe, Aldy Safruddin (Talenta Publisher, 2021)
Background: Sleep is a basic requirement of human beings. Sleeping brain is required to carry out adaptations to long-term structural and chemical needed to learn and remember. Rapid technological advances in recent times can reduce the duration of sleep especially in teenagers. A bad quality of sleep may affect cognitive function that will have an effect on students learning process. Objective: In general, this research aims to know the relationship between sleep quality with cognitive function of MAN Binjai student. Method: This research is a study of analytical method with cross sectional design. Data retrieval is performed only once for collecting primary data with the measuring instrument in the form of a questionnaire. Stratified random sampling technique was used to determine the number of samples. Results: on the analysis of correlation Sprearman obtained a value of 0.001 P (p< 0.05) indicating there is a relationship between sleep quality and cognitive function. The correlation coefficient (r) is -0.764, which indicates medium relationship between sleep quality and cognitive function of MAN Binjai student. Conclusion: There is a relationship that is directly proportional between the sleep quality with cognitive function in MAN Binjai students. Keywords: cognitive function, MoCA, PSQI, sleep quality, student Latar Belakang: Tidur merupakan kebutuhan pokok manusia. Tidur diperlukan otak untuk melaksanakan penyesuaian-penyesuaian kimiawi dan struktural jangka panjang yang diperlukan untuk belajar dan mengingat. Kemajuan teknologi yang begitu pesat belakangan ini dapat mengurangi durasi tidur terutama pada remaja. Kualitas tidur yang buruk dapat memengaruhi fungsi kognitif yang akan berpengaruh terhadap proses belajar siswa. Tujuan: Secara umum penelitian ini bertujuan untuk mengetahui hubungan kualitas tidur dengan fungsi kognitif siswa MAN Binjai. Metode: Penelitian ini merupakan penelitian dengan metode analitik dengan desain penelitian potong lintang. Pengambilan data dilakukan hanya sekali untuk mengumpulkan data primer dengan alat ukur berupa kuesioner MoCA dan PSQI. Teknik stratified random sampling digunakan untuk menentukan jumlah sampel. Sampel berjumlah 60 orang. Korelasi spearman digunakan dalam analisis data. Hasil: Dari studi didapatkan r = -0.76(p<0.05) yang menunjukkan adanya korelasi sedang dan berbanding terbalik antara kuesioner M0CA dan PSQI. Kesimpulan: Terdapat hubungan antara kualitas tidur dengan fungsi kognitif pada siswa MAN Binjai. Kata Kunci: fungsi kognitif, kualitas tidur, MoCA, PSQI, siswa